Borna disease virus phosphoprotein triggers the organization of viral inclusion bodies by liquid-liquid phase separation - Hirai, Yuya; Tomonaga, Keizo; Horie, Masayuki (International journal of biological macromolecules, 2021)
Inclusion bodies (IBs) are characteristic biomolecular condensates organized by the non-segmented negative-strand RNA viruses belonging to the order Mononegavirales. Although recent studies have revealed the characteristics of IBs formed by cytoplasmic mononegaviruses, that of Borna disease virus 1 (BoDV-1), a unique mononegavirus that forms IBs in the cell nucleus and establishes persistent infection remains elusive. Here, we characterize the IBs of BoDV-1 in terms of liquid-liquid phase separation (LLPS). The BoDV-1 phosphoprotein (P) alone induces LLPS and the nucleoprotein (N) is incorporated into the P droplets in vitro. In contrast, co-expression of N and P is required for the formation of IB-like structure in cells. Furthermore, while BoDV-1 P binds to RNA, an excess amount of RNA dissolves the liquid droplets formed by N and P in vitro. Notably, the intrinsically disordered N-terminal region of BoDV-1 P is essential to drive LLPS and to bind to RNA, suggesting that both abilities could compete with one another. These features are unique among mononegaviruses, and thus this study will contribute to a deeper understanding of LLPS-driven organization and RNA-mediated regulation of biomolecular condensates.